Audiovestibular findings in patients with Vogt-Koyanagi-Harada disease. (April 2014) - Noguchi, Yoshihiro; Nishio, Ayako; Takase, Hiroshi; Miyanaga, Masaru; Takahashi, Hiroyuki; Mochizuki, Manabu; Kitamura, Ken
Abstract Conclusion: The long-term follow-up study revealed a good audiovestibular prognosis in our patients with Vogt-Koyanagi-Harada disease (VKH) after adequate treatment. Objectives: To evaluate the audiovestibular findings and long-term prognosis of patients with VKH. Methods: A total of 82 ears in 41 patients (9 males and 32 females, aged 18–78 years) with VKH were examined in the audiovestibular study. Of the 41 patients, 16 patients with follow-up periods of more than 12 months (13–158 months) were included in the long-term follow-up study. Audiovestibular examinations included pure-tone audiometry; positional, positioning, and spontaneous nystagmus tests; and a caloric test. Results: Among the 41 patients, 28 (68%) complained of auditory symptoms at the initial visit and 28 (68%) showed sensorineural hearing loss (SNHL). Of the 24 patients who underwent nystagmus tests, only 3 (13%) presented with vestibular symptoms whereas 11 (46%) had nystagmus. Among 32 ears in 16 patients enrolled in the long-term follow-up study, 19 ears showed SNHL at the initial visit. The SNHL returned to normal in 14 ears (74%) and remained minimal in severity in the other 5 ears (26%) at the last visit. None of the patients showed persistent or repetitive vestibular symptoms.